Influence of the spacing between NSM-CFRP laminates on the flexural strengthening efficacy of RC slabs - Bonaldo, Everaldo (2007)
Fundação para a Ciência e a Tecnologia (FCT) - bolsa de doutoramento SFRH / BD / 11232 / 2002.